LEXICAL SUBSTITUTION IN ANTI-PROVERBS - Давлятшина Гульнур Юрисовна (American Journals, 2024)
This article examines proverbs and their lexical substitutions. In the modern world, there is a rapid linguistic creativity in the Russian language. In the mass media, in various societies and especially in the Internet space, a variety of word games are widely used, unexpected new formations are used.
Keywords: Substituteion, lexical substitutions, effect, education.